Factors Influencing Organizational Commitment among Nurse Managers of Labour and Delivery Departments at the Secondary Level Hospitals Affiliated to the Thai Ministry of Public Health - Phimchaisai, Punyanut; Wongchantorn, Nongnaphat; Srinon, Rassamee (Journal of Health Science and Alternative Medicine, 2024)
Introduction: Organizational commitment is an essential component that leads the delivery department to accomplish its goals, promote organizational efficiency and effectiveness, and improve the quality of healthcare services for mothers and children. This study aimed to identify and predict factors associated with organizational commitment among nurse managers of labor and delivery departments at the secondary-level hospitals affiliated with the Thai Ministry of Public Health (MOPH). Methods: A correlational predictive design was applied to collect data in obstetricians-managed and treated health conditions associated with prenatal, intrapartum, and postpartum care in the secondary-level hospitals based on MOPH’s E-service plan, F1- 77 hospitals (first-level) and M2 -88 hospitals (middle-level). Questionnaires were used to collect personal characteristics and information on organizational commitment. There were 17 items to collect data on three dimensions of organizational commitment: affective, continuance, and normative organizational commitment. Seven experts detected the questionnaire’s content validity using a content validity index (CVI) of 0.94, and Cronbach’s reliability coefficient of the questionnaires was 0.84. Data were collected and analyzed using descriptive statistics. Pearson product-moment correlation and stepwise multiple regression were used for the analyses. Results: A total of 238 nurse managers from 119 labor and delivery departments at the secondary level hospitals based on MOPH’s E-service plan, F1- 77 hospitals (first-level) and M2 -88 hospitals (middle-level) were recruited into the study. Age and education were significantly correlated at p-value<0.010 (r=0.20, r=0.23) and predicted an 8.6% variance in organizational commitment (R2 =0.086, p-value <0.010). They also significantly predicted 13.1% and 10.1% of the variance in affective and normative organizational commitment (R2=0.131, p-value<0.001; R2=0.101, p-value<0.010). The strongest influencing of organizational commitment was education level (β=0.21, p-value<0.010), and it was also the best predictor of organizational commitment (β =0.17, p-value< 0.010). Conclusion: The midwifery nurse administrative of the delivery unit should be concerned with affective and normative organizational commitment. Enhancing continuing education at higher educational levels or taking a short training course could promote a better practice of maternal and midwifery care.